El derecho a la resistencia, y su incidencia en la realidad jurídica del Ecuador. - Jiménez Vergara, Leonardo David (2013)
The present work of legal research entitled "The right to resistance, and its impact on the legal reality of Ecuador", has been done based on an arduous and extensive research, I must indicate that in this work a considerable sample was surveyed statistics of leaders of social organizations, Fiscal Agents, and Judges of Criminal Guarantees; as well as several interviews were carried out with the actors involved in our topic, having to point out that their contributions were very important for the analysis of the Right to Resistance, in the face of the violation and criminalization that exists of this constitutional right, due to the improper application and disproportionate to the criminal norm, actions that would be restricting the exercise of this constitutional right, by people, and leaders of social organizations, for the fear of being labeled saboteurs or terrorists, legal figures that have been applied frequently in recent years to these people who have protested or exercised resistance in defense of their rights. The work done in this legal research work has given us positive results, based on a technical and statistical analysis, and also because of the constant search for doctrinal and theoretical foundation, which has allowed us to design a coherent and legally valid proposal. adding an unnumbered article to the Criminal Code, in order to achieve, and avoid unduly and disproportionately applying the legal figures of crimes against State Security, especially those of sabotage and terrorism, when people, and leaders of social organizations, they have exercised the constitutional right to resistance; This proposal is also strengthened by the field research carried out, which allowed us to verify the hypothesis raised, and at the same time appreciate that it is important to introduce this article to the Criminal Code, in order to avoid unduly and disproportionately applying the legal acts of sabotage and terrorism, against people, and social leaders, who have exercised their constitutional right to resistance.